Asas Itikad Baik sebagai Dasar Hukum Pembatalan Merek: Studi Kasus Minyak Kutus Kutus - Ni Ketut Putri Pradnya Swari (Lembaga Pengembangan Kinerja Dosen, 2026)
The principle of good faith constitutes a fundamental element within Indonesia’s trademark law system, particularly in processes ranging from trademark registration to the cancellation of registered marks. This study examines the role of the good faith principle as a primary legal foundation for trademark annulment, using the dispute over the Minyak Kutus Kutus trademark as a case study. The conflict emerged when the trademark was registered by an individual who was not the original creator, leading to legal disputes and judicial examination. This research adopts a normative juridical method by analyzing various legal sources, including statutory regulations, court decisions, and relevant legal doctrines. The findings indicate that the principle of good faith is not merely an ethical norm but also functions as an important legal instrument to protect the legitimate rights of original trademark owners from attempts of unlawful control through bad-faith registration. Furthermore, the court’s decision in the Kutus Kutus case demonstrates the crucial role of enforcing the good faith principle in maintaining legal certainty while ensuring protection for fair and honest business actors in Indonesia’s trademark system.